Laugh and learn about childbirth [videorecording (DVD)]. - Bayles, Sheri (Expect This L.L.C., 2007)
Childbirth expert Sheri Bayles, RN, covers all aspects of labor and delivery, including pain relieving options, Lamaze training, a breathing technique, natural childbirth, and everything you need to know about cord blood banking.